GLOBAL WARMING AND CONSTRUCTION ASPECTS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The manufacture of cements with several main constituents is of particular importance with regard to reducing climatically relevant CO2 emissions in the cement industry. This ecological aspect is not the only argument in favor of Portland composite cements. They are also viable alternatives to Portland cement from the technical point of view. Substitution of ordinary Portland cement (CEM I) by Portland composite cements (CEM II) and (CEM III), which clearly possess different chemical and mineralogical compositions, results in changes of their reaction behavior with additives like superplasticizers. A common admixture to CEM I in that sense is limestone (industrial CaCO3). Its interaction with polycarboxylates is ignored and its inertness is taken for granted. This study provides a systematic approach in order to better understand the interaction of these polymeric superplasticizers with CaCO3 by adsorption and zeta potential measurements. The results give some fundamental understanding in how far the cement industry can reduce the production of cement clinker by replacing it with limestone as admixture and consequently the CO2-emission is reduced, which is of high political and environmental interest.